2020
DOI: 10.1371/journal.pone.0235966
|View full text |Cite
|
Sign up to set email alerts
|

A multi-scale modelling framework combining musculoskeletal rigid-body simulations with adaptive finite element analyses, to evaluate the impact of femoral geometry on hip joint contact forces and femoral bone growth

Abstract: Multi-scale simulations, combining muscle and joint contact force (JCF) from musculoskeletal simulations with adaptive mechanobiological finite element analysis, allow to estimate musculoskeletal loading and predict femoral growth in children. Generic linearly scaled musculoskeletal models are commonly used. This approach, however, neglects subject-and age-specific musculoskeletal geometry, e.g. femoral neck-shaft angle (NSA) and anteversion angle (AVA). This study aimed to evaluate the impact of proximal femo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
54
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 43 publications
9
54
1
2
Order By: Relevance
“…The hip JRFs trend monotonically increasing with anteversion angle is consistent with those reported by Kainz et al [10] using a commercial bone-deformation tool and by Heller et al [9] using a different MSK modelling approach. Our hip JRF magnitudes are comparable to [5, 10] and, as in those studies, they are larger than in vivo measurements [1]. In previous literature this overestimation has been attributed to the simplified anatomical representation of the hip muscle anatomy [15].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The hip JRFs trend monotonically increasing with anteversion angle is consistent with those reported by Kainz et al [10] using a commercial bone-deformation tool and by Heller et al [9] using a different MSK modelling approach. Our hip JRF magnitudes are comparable to [5, 10] and, as in those studies, they are larger than in vivo measurements [1]. In previous literature this overestimation has been attributed to the simplified anatomical representation of the hip muscle anatomy [15].…”
Section: Discussionsupporting
confidence: 90%
“…A systematic quantification of the impact of this lack of personalization on the accuracy of joint reaction forces (JRFs) is unavailable in previous MSK modelling literature [7]. For example, femoral anteversion, the angle between the femoral neck axis and the posterior condylar axis, has been previously shown to affect muscle moment arms in children affected by cerebral palsy [8] and to influence the hip JRFs in hip replacement patients [9] and typically developing children [10], however, its effect on the knee and ankle joints remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…A multi-scale modelling approach, which combines musculoskeletal simulations with mechanobiological finite element analysis, can be used to predict femoral growth trends (Carriero et al, 2011;Kainz et al, 2020;Yadav et al, 2016). Carriero et al (2011) simulated femoral growth and confirmed increased NSA and AVA in three children with CP when compared to a TD child.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, there is a lack of understanding in the variability of bone and joint forces due to different anatomies [ 20 ]. The ability to explore intra-personal variations within multiple subjects is necessary to investigate how individual anatomical parameters, motion patterns, and other factors (such as age and weight) affect the bone and joint force estimations [ 26 ], and subsequently how these would influence the predicted strain patterns on the femur, when combined with an individual specific organ level finite element model of the bone.…”
Section: Introductionmentioning
confidence: 99%